GAMBARAN KADAR KOLESTEROL LOW DENSITY LIPOPROTEIN (LDL) PADA KOMUNITAS LACTO VEGETARIAN BRAHMA KUMARIS DI KOTA DENPASAR - Ni Putu Yuliartini; I Putu Oka Dharmawan; Putu Ayu Parwati (Bali Medika Jurnal, 2017)
Coronary Heart Disease (CHD) is one of the main factors of cardiovascular disiase (Heart and blood vassel disease) one the leading cause of death in developed an developing country. One barometer in orther to know the risk factor for CHD is the lipid profile, inkluding Low Density Lipoprotein (LDL) cholesterol. This causes many people to switch to adopt a vegetarian diet. Lacto vegetarians consume foods from vegetable, vegetables and fruits, this type of vegetarians consume milk but don’t consume eggs. The goal of this study is to know the level of Low Density Lipoprotein (LDL) on lacto vegetarian in Brahma Kumaris community. The type of study is descriptive and using puposive sampling tecnique. Sampling was done in the Lacto Vegetarian Brahma Kumaris community. LDL examination results obtained from 30 respondents, this is 28 people (93.4%) with optimal levels, 1 person (3.3%) with levels close to optimal, and 1 person (3.3%) with alarming levels.